Elastic deformation in ceria nanorods via a fluorite-to-rutile phase transition - Sayle, Thi X. T.; Sayle, Dean C. (American Chemical Society, 2010)
Atomistic simulations reveal that ceria nanorods, under uniaxial tension, can accommodate over 6% elastic deformation. Moreover, a reversible fluorite-to- rutile phase change occurs above 6% strain for a ceria nanorod that extends along [110]. We also observe that during unloading the stress increases with decreasing strain as the rutile reverts back to fluorite. Ceria nanorods may find possible application as vehicles for elastic energy storage.
Keywords: atomistic simulation; microstructure; molecular dynamics; nanoenergy storage